Computational assessment of the impact of Cu(II) and Al(III) on β-amyloid42 fibrils: Binding sites, structural stability, and possible physiological implications - Roldán-Martín, Lorena; Sodupe, Mariona; Maréchal, Jean-Didier (Frontiers in Neuroscience, 2023)
One of the Alzheimer’s Disease major hallmarks is the aggregation of -amyloid peptide, a process in which metal ions play an important role. In the present work, an integrative computational study has been performed to identify metal-binding regions and determine the conformational impact of Cu(II) and Al(III) ion binding to the -amyloid (A42) fibrillar structure. Through classical and gaussian accelerated molecular dynamics, it has been observed that the metal-free fiber shows a hinge fan-like motion of the S-shape structure, maintaining the general conformation. Upon metal coordination, distinctive patterns are observed depending on the metal. Cu(II) binds to the flexible N-terminal region and induces structural changes that could ultimately disrupt the fibrillar structure. On the contrary, Al(III) binding takes place with residues Glu22 and Asp23, and its binding reinforces the core stability of the system. These results give clues on the molecular impact of the interaction of metal ions with the aggregates and sustain their non-innocent roles in the evolution of the illness.